Turbulent Times Demand Dynamic Rules - Hannah, David; Zatzick, Christopher; Kietzmann, Jan (MIT Sloan Management Review, 2021)
To prosper in dynamic times, businesses need to change their approach to rule-making and adherence. To transition to creating dynamic rules - rules that are built to change through collaboration, experimentation, and learning - leaders must help spread the correct mindset throughout their organizations. There are three specific steps that leaders should take to facilitate that shift: Increase employee involvement in rule-making, embrace rapid experimentation, and enact rule audits.